Phenomenological origin of "care" and importance of the concept of time in nursing history - José Siles González; María del Carmen Solano Ruiz (Universidad de Alicante, 2012)
The general aim of this work consists, fundamentally, in meditate on the time concept in the cares context, facilitating the understanding of the phenomenological nursing nature, and also, to analyze historically the phenomenological origin of the concepts of "care" and "cure" identifying its presence and meaning in the myths. Considering that the phenomenological nature of cares is described and explained in oral traditions integrated in myths and fables, constitutes the hypothesis of this study. Results: Heidegger employs narrative materials as the fable to develop the concepts of care and cure and integrate them in its henomenological work. The care is a concept whose great epistemologic potential can contribute to the process of consolidation of the nursing discipline. Conclusions: Heidegger, in "Being and Time", develop the phenomenological concept of "care" and "cure" in a narrative source like the fable of Higinio (S. I a.C) "Fable of the man and the world", Time constitutes the existential riverbed for which there pass the diverse historical moments or "Kairós" that the human being (at individual, family or community level) dedicates to the satisfaction of each and every of his needs.